TIONGHOA MUSLIM DI MADURA: Asimilasi Budaya dan Interaksi Sosial - Akhmad Siddiq; Mutamakkin Billa (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Assimilation is a process of dynamic communication and mutual influence between two cultures, which grow together and adapt to each other. In the Madurese context, social interaction and cultural assimilation between the Chinese community and Madurese society develops in a complex and diverse social space, depending on the historical and sociological context. One example of cultural assimilation in Madura is the attachment of cultural adaptation by Chinese Muslims on the one hand and the attachment of Chinese art and architecture to Madurese cultural works on the other. This study intends to explain the existence of Chinese Muslims in Madura, both from historical and sociological perspective, as well as their struggles amid the flow of Madurese culture which is perceived as Islamic culture. It is hoped that this research topic can contribute to the discourse on social identity, religion and ethnicity. In addition, this qualitative research, that is based on observation and in-depth interviews, is expected to elucidate a piece of social interaction and cultural assimilation among Chinese Muslims in Madura.